PELATIHAN PENGOLAHAN BAWANG GORENG KEMASAN DIDESA HUHAK KECAMATAN PAGIMANA KABUPATEN BANGGAI - Wirnangsi Din Uno (Jambura Journal of Husbandry and Agriculture Community Serve (JJHCS), 2021)
Community empowerment is a process in which people, especially those who lack access to development resources, are encouraged to increase their independence in developing their lives. The main superior products in Huhak Village are fish and shallots which are cultivated by farmers. The prospect of onion farming is said to be quite bright. Through this shallot processing training, apart from helping the marketing of shallot farmers, it can also reduce the unemployment rate in the area around the industry. The target is the realization of a processing and marketing system that is able to guarantee price stability and the availability of quality shallots independently. Training activities for youth cadres of Huhak village, Pagimana District, Banggai Regency, Central Sulawesi Province went smoothly and in accordance with the expected target, namely increasing public awareness about the function and role of village youth cadres in terms of seeking community agricultural products, especially in processing red onions in packaging so that these expectations can be achieved well.